Organizing heritage-tree landscape-perception and CES representations in a historic district: A node–time–touchpoint approach - Fengshang Chen; Qingjun He; Wei Wang; Guoyu Wang; Yuqing Feng (Journal of Environmental Management, 2026)

Effect of water immersion time on nanoindentation creep behavior of marl - Bo Hu; Xianqi Qin; Mengru Zeng; Yugang Cheng; Xuefu Zhang; Zhiqiang Lv; Qingjun He; Chunyong Jiang; Xi Long; Jian Mu; Jianlong Cheng (Bulletin of Engineering Geology and the Environment, 2026)

Study on the mechanism of heavy oil low-temperature upgrading based on multi-component synergy - Zengrun Xie; Jian Hou; Teng Lu; Lixiong He; Zezheng Sun; Xinge Sun; Chihui Luo; Weibing Tian; Qingjun Du; Yongge Liu; Bei Wei (Chemical Engineering Journal, 2026)

Multi-scale Investigation of Mudstone Swelling Behavior Under Hydrochemical Conditions - Qingjun Zuo; Mengjian Yang; Pan Li; Qinglin Yi; Yiliang Liu; Biao Wang; Xuefeng He (Geotechnical and Geological Engineering, 2026)

Decoding PM2.5 oxidative potential in Ningbo, China: Key chemicals, sources, and health risks via dual-assay and machine learning - Lord Famiyeh; Ke Chen; Jingsha Xu; Fiseha Berhanu Tesema; Mosses Solomon; Dongsheng Ji; Honghui Xu; Chengjun Wang; Qingjun Guo; Conghua Wen; John L. Zhou; Jun He (Journal of Hazardous Materials, 2025)

The multifaceted nature of SUMOylation in heart disease and its therapeutic potential - Ying He; Zhijie Yang; Dan Guo; Cheng Luo; Qiaoqiao Liu; Lei Xian; Fan Yang; Chusheng Huang; Qingjun Wei (Molecular and Cellular Biochemistry, 2025)

Rainfall-triggered evolution of deformation patterns and catastrophic mechanisms in soil-rock mixture slopes - Qingjun Zuo; Xuefeng He; Zhongquan Luo; Yonghuang Deng; Ziyi Xu; Duanmiao Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Comparation of pheromone-binding proteins 1 and 2 of Spodoptera frugiperda in perceiving the three sex pheromone components Z9-14:Ac, Z7-12: Ac and Z11-16: Ac - Liming Hu; Taoli Zhang; Qingjun Wu; Kangyuan Liang; Guohui Yu; Muyang He; Dasong Chen; Xiangning Su; Yuping Zhang; Zhenfei Zhang; Jianmei Shen (Pesticide Biochemistry and Physiology, 2024)

Utilization of steel slag in air pollution and greenhouse gas emission reduction-application, mechanism and challenge: A review - Yuncong He; Shaohua Jia; Honghong Yi; Xiaolong Tang; Qingjun Yu; Fengyu Gao; Dongjuan Kang; Shunzheng Zhao (Journal of Environmental Chemical Engineering, 2024)

Corrigendum to “Size distribution and lung-depostion of ambient particulate matter oxidative potential: A contrast between dithiothreitol and ascorbic acid assays” [Environ. Pollut. 336 (2023) 122437] - Lord Famiyeh; Chunrong Jia; Ke Chen; Yu-Ting Tang; Dongsheng Ji; Jun He; Qingjun Guo (Environmental Pollution, 2024)

Effect of Ce0.6Zr0.4O2 nanocrystals on boosting hydrogen storage performance of MgH2 - Houqun Xiao; Fangren Qian; Xiaoxuan Zhang; Huazhou Hu; Ruizhu Tang; Chengsi Hu; Wenhao Zhou; Xincong He; Zonghua Pu; Chuanming Ma; Ruixiang Wang; Luocai Yi; et al. (Chemical Engineering Journal, 2024)

Status and Challenges of Marine Current Turbines: A Global Review - Yajing Gu; Tian Zou; Hongwei Liu; Yonggang Lin; He Ren; Qingjun Li (Journal of Marine Science and Engineering, 2024)
Over the past few decades, marine current energy utilization has transitioned from conceptual demonstrations to industrial-scale prototypes. This progression now approaches a crucial phase emphasizing the need for industrialization and commercialization. This paper provides an in-depth examination of the developmental status of large-scale marine current turbines and arrays, underscoring the promising prospects for marine current energy systems. Despite the significant advancements, the deployment of these systems has revealed several challenges, including blade design optimization, transmission system selection, and the establishment of appropriate test sites. Addressing these issues is essential for technological maturity and economic feasibility, which will foster the next wave of innovation in marine energy systems. Furthermore, the paper offers various perspectives for future applications.

Breathing in danger: Unveiling the link between human exposure to outdoor PM2.5-bound polycyclic aromatic hydrocarbons and lung cancer risk in an urban residential area of China - Lord Famiyeh; Honghui Xu; Ke Chen; Yu-Ting Tang; Dongsheng Ji; Hang Xiao; Lei Tong; Chunrong Jia; Qingjun Guo; Jun He (Science of The Total Environment, 2024)

Size distribution and lung-deposition of ambient particulate matter oxidative potential: A contrast between dithiothreitol and ascorbic acid assays - Lord Famiyeh; Chunrong Jia; Ke Chen; Yu-Ting Tang; Dongsheng Ji; Jun He; Qingjun Guo (Environmental Pollution, 2023)

Effects of attapulgite on the growth status of submerged macrophytes Vallisneria spiralis and sediment microenvironment - Rou Wang; Jiying Zhu; Beining Li; Yunli Liu; Qingjun Fang; Guoliang Bai; Yadong Tang; Feng He; Qiaohong Zhou; Zhenbin Wu; Yi Zhang (Journal of Environmental Management, 2023)

Electrocoagulation coupled with electrooxidation for the simultaneous treatment of multiple pollutants in contaminated sediments - Qingjun Zeng; Yifan Zhang; Pingshan Chen; Yuting He; Congli Yi; Chunhua Feng (Journal of Environmental Sciences, 2023)

Research and application of method of oxygen isotope of inorganic phosphate in Beijing agricultural soils - Liyan Tian; Qingjun Guo; Yongguan Zhu; Huijun He; Yunchao Lang; Jian Hu; Han Zhang; Rongfei Wei; Xiaokun Han; Marc Peters; Junxing Yang (Environmental Science and Pollution Research, 2016)

miR-526a regulates apoptotic cell growth in human carcinoma cells - Xiaoli Yang; Cui Wang; Changzhi Xu; Zhifeng Yan; Congwen Wei; Kai Guan; Shengli Ma; Ye Cao; Liping Liu; Deyong Zou; Xiang He; Buchang Zhang; et al. (Molecular and Cellular Biochemistry, 2015)

Proliferating cell nuclear antigen destabilizes c-Abl tyrosine kinase and regulates cell apoptosis in response to DNA damage - Xiang He; Congwen Wei; Ting Song; Jing Yuan; Yanhong Zhang; Qingjun Ma; Wei Shi; Hui Zhong (Apoptosis, 2009)